2019
DOI: 10.1136/bmj.l4340
|View full text |Cite|
|
Sign up to set email alerts
|

New drugs: where did we go wrong and what can we do better?

Abstract: More than half of new drugs entering the German healthcare system have not been shown to add benefit. Beate Wieseler and colleagues argue that international drug development processes and policies are responsible and must be reformed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 29 publications
2
87
1
8
Order By: Relevance
“…The views of the interviewed experts align strongly with the sentiments expressed by authors in the field and confirm many of the problems described in the literature. For instance, the current drug development framework has indeed been described as insufficiently patient-centered (Mullins et al, 2014;Ioannidis, 2016;Lacombe et al, 2019b;Wieseler et al, 2019) and unable to produce fit-for-purpose RWE (Kempf et al, 2017). Nevertheless, a notable discrepancy between our findings and the strategies proposed by Lacombe et al (2019b) is that most of the interviewees who explicitly favored a particular setting in which such research could take place were reluctant to endorse the international approach advocated by the latter.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The views of the interviewed experts align strongly with the sentiments expressed by authors in the field and confirm many of the problems described in the literature. For instance, the current drug development framework has indeed been described as insufficiently patient-centered (Mullins et al, 2014;Ioannidis, 2016;Lacombe et al, 2019b;Wieseler et al, 2019) and unable to produce fit-for-purpose RWE (Kempf et al, 2017). Nevertheless, a notable discrepancy between our findings and the strategies proposed by Lacombe et al (2019b) is that most of the interviewees who explicitly favored a particular setting in which such research could take place were reluctant to endorse the international approach advocated by the latter.…”
Section: Discussioncontrasting
confidence: 73%
“…In recent years however, this paradigm has faced criticism from authors in the field (Mullins et al, 2014;Ioannidis, 2016;Lacombe et al, 2019b;Wieseler et al, 2019) for being too drugcentered and/or for not sufficiently focusing on the patients who will eventually receive the treatment in real-world clinical practice. The existing clinical development framework allows the industry to primarily pursue regulatory approval of their products without taking into account the real needs of patients and society (Lacombe et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have argued that most new drugs in general, and most new cancer drugs in particular, have not provided real advances over existing drugs. Wieseler, McGauran, and Kaiser said that the proportion of 'true innovation' is less than 15% [18]. Davis et al said that most cancer drugs approved by the EMA between 2009 and 2013 had been approved with no evidence of clinically meaningful benefit on patient relevant outcomes (survival and quality of life) [19].…”
Section: Expert Opinionmentioning
confidence: 99%
“…First, more than half of U.S. funding for biomedical research came from pharmaceutical and biotechnology firms [38]. 18 Much of the rest came from the federal government (i.e. the NIH), and new drugs often build on upstream government research [39].…”
Section: Orcidmentioning
confidence: 99%
“…[1][2][3][4][5][6] In a cohort of 216 drugs approved by the German drug regulatory authority between 2011 and 2016, the independent Institute for Quality and Efficiency in Health Care (IQWiG) judged that 22 (10 %) new drugs had substantial benefits compared to already available treatments, while 125 (58 %) drugs had no proof of added benefits. 1 Cohort studies of oncology drugs approved by the European Medicines Agency (EMA) 4 and the US Food and Drug Administration (FDA) 5 found that most drugs were approved without evidence of benefits on overall mortality or quality of life. Similarly, an analysis of oncology drugs approved by the EMA between 2014 and 2016 reported that many pivotal trials underpinning drug approvals were of high risk of bias due to problems with the trial design and or trial conduct.…”
Section: Introductionmentioning
confidence: 99%